The Effect of Accounts Receivable Turnover, Cash Turnover, and Inventory Turnover on Profitability (A Study of Consumer Goods Industry Companies Listed on the Indonesia Stock Exchange for the Period 2022-2024) - Dita Apriliana; Elok Vilantika (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the effect of Accounts Receivable Turnover, Cash Turnover, and Inventory Turnover on Profitability. The sample in this research consists of 47 consumer goods industry companies listed on the Indonesia Stock Exchange during 2022–2024. The research method uses a quantitative approach with multiple linear regression analysis. The results show that, partially, accounts receivable turnover has a significant effect on profitability. Cash turnover also has a significant effect on profitability. Likewise, inventory turnover partially has a significant effect on profitability. Simultaneously, accounts receivable turnover, cash turnover, and inventory turnover significantly affect profitability with an F-value of 7.379, which is greater than the F-table value of 2.67, and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.14 indicates that the independent variables can explain 14% of the variation in profitability, while the remaining is influenced by other variables outside this study.